Doutoramento performático: narrações do eu morrente em hibridações poéticas - Oliveira, Valdemir de (2024)
The research Performative Doctorate: narrations of the dying self in poetic hybridizations is part of the Art and Technology research line of the Postgraduate Program in Visual Arts - PPGART at the Federal University of Santa Maria - UFSM. It is a research project in visual poetics whose object of investigation is the manipulation of (wandering) personal narratives for artistic production by means of hybrid heuristic processes of creation. It is based on a research experience in art, reordering elements of narrative research and genetic criticism, using hybrid heuristic procedures. Bringing together authors such as Agnus Valente, Nicolas Bourriaud, Jean D. Clandinin, F. Michael Connelly, Byung-Chul Han, Sandra Rey, Icleia Barbosa Cattani, among others, considers the fluidity of investigative processes in this field as a space for the construction and experimentation of personalized procedures of the artistic making of the artist-researcher, defended as a research that narrates through hybrid methodological procedures for the development of creative processes in visual poetics, thought of as hybridization in creation, this was called Artistic Protomanipulations, which generated a set of Protocreations that were organized into twenty-five series/sets selected, involving, among other processes, installations, performances, objects, photoperformance and video dance, mobilized by situations of context, presence and being in transit. Using equally hybrid analysis protocols, the Protocreations generated were cataloged according to specific criteria. The research carried out results in considerations about an (in)conclusion from the perspective of a creative experience in process that extends in the direction of the time of existence of the "dying self", reflecting on the specificities and singularities involved in poetic research, as a generator of narratives that are always unique